Empirical analysis of the relationship of investment and innovative activity of regions of Russia - Igor Aleksandrovich Bayev; Irina Aleksandrovna Solovyova (Экономика региона, 2014)
The article is devoted to the study of the relationship of innovation and investment activity of Russian regions. On the basis of the statistical data, the system of indicators and designed complex indices of innovation and investment activity of regions are proved. The level of investment and innovative activity of regions in the last four years are analyzed, the basic tendencies and structural changes are revealed. The dependence between innovation and investment activity of regions is investigated. Based on the analysis, the map of the region’s position demonstrating the high level of differentiation of Russian regions in terms of both investment and innovation activity is developed. Also, the authors proposed a matrix distributing regions into four groups depending on the correlation between a level of innovation and investment activity, and recommendations on the selection of priority directions of economic policy for the subjects of the Russian Federation taking into account their current position are developed. The research results have practical significance and can be used to improve existing regional economic development programs for both individual regions and the country as a whole.